Transformation of the Quality of Hidayatullah College Graduates: Between Academic Competence and Islamic Character in the Riau Islands - Khoirul Amri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the transformation in the quality of graduates from Hidayatullah College in the Riau Islands Province, focusing on two main aspects: academic competence and Islamic character. The research method used is a mixed-method approach, combining a quantitative component through the distribution of questionnaires to final-year students and alumni (350 respondents) with a qualitative component through interviews with lecturers and graduate users (25 respondents). The study's results demonstrate academic competence. 72% of alumni stated that the course material is relevant to the needs of the world of work, especially in the fields of Islamic education, da'wah management, and Islamic economics. Twenty-eight percent consider the curriculum too theoretical. In terms of Islamic character, the study found that 82% of respondents have discipline in carrying out worship, 85% received positive appreciation from graduate users regarding social morals, and 62% are involved in Islamic leadership activities. This study implies that Hidayatullah College in the Riau Islands has successfully transformed the quality of its graduates by emphasizing strong Islamic character aspects. Therefore, it is necessary to develop a more comprehensive educational model that focuses not only on the religiosity aspect but also on the relevance of graduates.